The Influence of the Logan Avenue Problem-Solving – Heuristic Model on the Mathematical Reasoning Ability of Grade VIII Students of Haruru Christian Middle School - Mursaid Dahlan; Ivatul Laily Kurniawati; Dhamas Mega Amarlita; Junardin Muhamad Masihu (Al-Musannif, 2026)
The purpose of this study was to determine whether there was any influence of the Logan Avenue Problem Solving Heuristic Model on the Mathematical Reasoning Ability of Class VIII Students of Haruru Christian Middle School, Amahai District, Central Maluku Regency.The method used in this study is a quasi-experimental method that is tested quantitatively. The population of this study was Class VIII class of Haruru Christian Middle School, Amahai District, Central Maluku Regency. The sampling technique used the Non-equivalent posttest only control group design technique. Class VIII1 students as the experimental class were given the Logan Avenue Problem Solving Heuristic model treatment and students in class VIII2 as the control class were given the Direct Learning model treatment. The calculation results obtained the average score of students from the experimental class = 82.82, while the average score of students from the control class = 58.6. Based on the normality test and homogeneity test of the two groups, it was found that the sample data were normally distributed and homogeneous so that the t test was used to test the hypothesis. The calculation results show t count =8.6975> t_table = 2.02108 at a significance level of α = 0.05. Thus H0“is rejected” and “H1 is accepted”. It means “There is an Influence of the Heuristic Logan Avenue Problem Solving Model on the Mathematical Reasoning Ability of Class VIII Students of Haruru Christian Middle School, Amahai District, Central Maluku Regency.